Integrating AI-Based Tools to Support Students’ Argumentative Writing Development - Siti Maria Ulfa; Tera Athena; Mariyatul Kiptiyah; Iin Rachmawati; Maulana Yusuf Aditya (Asosiasi Pengelola Publikasi Ilmiah (APPI) PT PGRI, 2025)
This study explores the integration of Artificial Intelligence (AI)-based tools in supporting university students’ development of argumentative writing skills in an English as a Foreign Language (EFL) context. Writing an argumentative text requires students to construct clear thesis statements, justify arguments with credible evidence, and ensure logical coherence throughout the text. A qualitative descriptive design was employed involving undergraduate EFL students who utilized AI-supported applications, such as AI writing assistants and automated feedback tools, during a series of writing activities. Data were gathered through students’ written products, classroom observations, and semi-structured interviews. The results show that the use of AI-based tools enhances students’ accuracy, idea organization, and lexical choices, particularly in improving their argument clarity and cohesion. However, the findings also reveal students’ dependency on AI suggestions, indicating the need for critical awareness in using AI responsibly. The study concludes that AI-based tools can serve as effective learning support when used under guided instruction, promoting students’ argumentative writing competence and autonomy.